2017
DOI: 10.1002/jmrs.223
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐energy CT in gout – A review of current concepts and applications

Abstract: Dual‐energy computed tomography (DECT) is a relatively recent development in the imaging of gouty arthritis. Its availability and usage have become increasingly widespread in recent years. DECT is a non‐invasive method for the visualisation, characterisation and quantification of monosodium urate crystal deposits which aids the clinician in the early diagnosis, treatment and follow‐up of this condition. This article aims to give an up to date review and summary of existing literature on the role and accuracy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
67
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 46 publications
0
67
0
5
Order By: Relevance
“…The diagnosis of gout has traditionally been based on patient history, clinical findings, laboratory, and/or joint aspirate results, with imaging as an adjunct (93). For typical presentations of gout, a clinical diagnosis alone is reasonably accurate but not definitive without crystal confirmation (94,95).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The diagnosis of gout has traditionally been based on patient history, clinical findings, laboratory, and/or joint aspirate results, with imaging as an adjunct (93). For typical presentations of gout, a clinical diagnosis alone is reasonably accurate but not definitive without crystal confirmation (94,95).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced images such as dual-energy computed tomography (DECT), MRI, and ultrasound have been useful in visualizing pathology resulting from gout. DECT can identify and quantify monosodium urate (MSU) crystals (93,102), whereas MRI is used to assess inflammation, bone erosion, and cartilage damage in gout (102). Low-quality evidence from 3 observational studies showed that DECT had a sensitivity of 85% to 100% with specificity of 83% to 92% for predicting gout (103).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MRI and CT investigations are considered non-specific, but may show homogenous changes on T1 and T2 imaging 11. Likewise, dual energy CT, which is used for identifying appendicular gout, is not ideal for imaging of spinal gout due to poor sensitivity for MSU crystals 12. The gold standard diagnosis is through biopsy of the spine and pathological analysis showing MSU crystals that are negatively birefringent under polarised light 1.…”
Section: Discussionmentioning
confidence: 99%